2023
DOI: 10.3390/foods12112269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Combination of Hibiscus sabdariffa in Combination with Other Plant Extracts in the Prevention of Metabolic Syndrome: A Systematic Review and Meta-Analysis

Abstract: Metabolic syndrome is a complex and multifactorial disorder associated with increased risk of cardiovascular disease and type 2 diabetes, exacerbated by a sedentary lifestyle and situations such as the COVID-19 pandemic. Recent studies have shown that consumption of fruits and vegetables high in polyphenols has a protective effect, reducing cardiovascular risk. Hibiscus sabdariffa (HS) in combination with other plant extracts has recently attracted scientists’ attention due to its potential use in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…In another study, Akber Aisa et al (2019) ( Aisa et al, 2019 ) found that Cicer arietinum L modulates glycemic response and regulates dyslipidemia. A systematic review and meta-analysis by García-Muñoz et al (2023) ( García-Muñoz et al, 2023 ) reported the effectiveness of Hibiscus sabdariffa in weight loss, reduction of fat tissue, lowering blood pressure, and improving lipid profiles. Apart from studies directly emphasizing the effects of plants on the main components of metabolic syndrome, some studies have also shown that plants can improve metabolic syndrome through antibacterial activities, antioxidant properties, anti-inflammatory activities, and reduction of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Akber Aisa et al (2019) ( Aisa et al, 2019 ) found that Cicer arietinum L modulates glycemic response and regulates dyslipidemia. A systematic review and meta-analysis by García-Muñoz et al (2023) ( García-Muñoz et al, 2023 ) reported the effectiveness of Hibiscus sabdariffa in weight loss, reduction of fat tissue, lowering blood pressure, and improving lipid profiles. Apart from studies directly emphasizing the effects of plants on the main components of metabolic syndrome, some studies have also shown that plants can improve metabolic syndrome through antibacterial activities, antioxidant properties, anti-inflammatory activities, and reduction of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis provides notable advantages, including cost-effectiveness and feasibility compared to large-scale trials. This approach has gained extensive use in food science, particularly in investigating prevention and treatment strategies for cardiovascular diseases [20][21][22][23][24][25]. Furthermore, network pharmacology, as a methodology that reevaluates existing drugs, aids in discovering the potential efficacy and mechanisms of drugs already approved for treating new diseases, thus reducing the time and cost of developing new drugs [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%